Understanding intergenerational characteristics of nurses in clinical practice - Ukmar, Neža (Obzornik zdravstvene nege, 2025)
Introduction: In the context of globally changing and multigenerational work environments, understanding generational differences is crucial for reducing conflict and improving collaboration in nursing care. The aim of this study was to explore the intergenerational characteristics of nurses in clinical practice.Methods: In this non-experimental, descriptive, quantitative study, a translated version of the Multidimensional Nursing Generations Questionnaire was used to assess generational differences in nursing. A convenience sample of 100 nurses working in the clinical setting was surveyed. A total of 91 respondents (91%) were women and 9 (9%) were men. The data were analysed using basic descriptive statistics and non-parametric statistical tests such as the Kruskal-Wallis test, the Mann-Whitney U test, and the one-sample Wilcoxon signed-rank test.Results: The results of the study indicate good coordination and collaboration between individual generations of respondents, a high degree of openness to change, autonomy and confidence in decision-making, and a positive attitude towards work (p 0.05).Discussion and conclusion: Our results indicate good intergenerational interaction and coordination among nursing professionals. The study contributes to a better understanding of the dynamics of intergenerational collaboration in nursing, which has the potential to improve working relationships and the quality of care.
Keywords: delovno okolje; intergenerational cooperation; kakovost; medgeneracijsko sodelovanje; nursing; quality; satisfaction; work environment; zadovoljstvo; zdravstvena nega